Quality and Innovation as Factors Influencing the Pricing Policy of Hotels in Historical Buildings in the Slovak Republic - Vanda ČIRČOVÁ; Jaroslava GBUROVÁ (Communications of International Proceedings, 2023)
In today's era of rapid technological change and increasing competition in the tourism industry, historic hotels have become unique destinations for discerning guests. Their unique charm and cultural heritage have attracted the attention of tourists from all over the world. However, despite their historicity, these hotels face complex challenges associated with modernisation and competition in today's domestic and global markets. The prices they set for their services have become key factors affecting their competitiveness and long-term sustainability. The aim of this paper is to analyze the impact of quality and innovation as factors influencing the price and pricing policies of hotels in historical buildings operating in the Slovak Republic from the perspective of consumers. The results of the paper will provide valuable insights for the hotel industry in the Slovak Republic and can serve as a guideline for hoteliers and managers in shaping a pricing policy that takes into account the expectations and preferences of consumers, while striving to strike a balance between preserving the historic character and providing innovative services.
Keywords: quality; innovation; pricing policy; historical buildings; hotels.